Calculation of Effective Molecules Collision Frequency and Cross-Sectional Ratio for Electromagnetic Discharge in Various Gases Mixtures - Mohammad, Kareem K (Al-Nahrain Journal of Science, 2018)
Estimation of gases quantities in gases mixture in plasma were accomplished at 300K. Each mixture has an effective value of the molecular collision frequency, electro-ions collision frequency and collision cross-sectional ratio. The computational and experimental results are correlated. In this work, the concept of separate control ion energy and ion flux by the two frequencies works generally well for the investigated discharge setup. The high frequency mainly determines ion flux and radical formation in the mixture discharges while ion energies are strongly influenced by the low frequency. Deviations from an ideally separated control of ion flux and energy are caused by influences on discharge parameters and interaction between the two frequencies since the radio frequency (RF) power sources are coupled to each other in the current setup.